Novel Albumin Nanoparticle Enhanced the Anti-Insulin-Resistant-Hepatoma Activity of Metformin - Lu Z (Dove Medical Press, 2020)
Zhong Lu,1,2 Li Qi,2 Ya-ru Lin,2 Lei Sun,2 Lin Zhang,2 Gui-chun Wang,2 Jia-qiu Li,2 Jin-ming Yu2 1Department of Radiation Oncology, Shandong Cancer Hospital Affiliated to Shandong University, Jinan 250117, People’s Republic of China; 2Department of Oncology, Clinical College of Weifang Medical University, Weifang 261031, People’s Republic of ChinaCorrespondence: Li QiDepartment of Oncology, Clinical College of Weifang Medical University, Weifang 261031, People’s Republic of ChinaTel +86 0536-3081263Email qili1104doc@126.comIntroduction: Metformin is an ideal candidate to treat the liver tumor with insulin resistance because of its good performance in the treatment of type 2 diabetes and the advantage in cancer therapy. We aim to develop a delivery system with higher efficiency than free drug.Methods: Metformin-bovine serum albumin (met-BSA) nanoparticles (NPs) were prepared using the anti-solvent precipitation method with a stabilizer of BSA for particle growth. The therapeutic effect of the drug was tested by the insulin-resistant HepG2 cells and C57BL/6J mice at a glucose starvation condition. The interaction mechanism of the drug and the protein during the formation of the NPs was tested using a series of spectroscopy.Results: Metformin and BSA formed nonporous and spherical particles of about 200 nm with proper lognormal distribution and thermostability. The cellular uptake, as well as the anti-liver cancer activities of met-BSA, was enhanced dramatically compared with the free drug. The thermodynamic studies suggested that the weak binding of metformin to BSA was governed by hydrogen bonds and van der Waals forces. Moreover, the results of synchronous, circular dichroism (CD) and three-dimensional fluorescence demonstrated that the BSA skeleton and chromophore microenvironments were changed in the presence of metformin.Conclusion: Therefore, met-BSA has been proved as a simple yet effective therapeutic agent for cancer with insulin resistance, promising for future clinic translations in cancer treatment.Keywords: liver cancer, metformin, bovine serum albumin, nanoparticle, spectroscopy